Highly effective and durable P-N synergistic flame retardant containing ammonium phosphate and phosphonate for cotton fabrics. (June 2022) - Ding, Dan; Liu, Yunlan; Lu, Yanfeng; Liao, Ying; Chen, Yu; Zhang, Guangxian; Zhang, Fengxiu
Highlights: APEHAP contains ammonium phosphate reactive groups, which can react with cotton fabrics to form P-O-C covalent bonds. APEHAP contains phosphonate groups, which reduce the substitution reactions with metal ions during washing. APEHAP-treated cotton exhibits excellent flame retardancy and durability. The mechanical properties of APEHAP-treated cotton remain good. Abstract: Cotton fabrics are widely used in everyday applications, which are flammable and present a fire hazard. Therefore, a phosphorus-nitrogen flame retardant, pentaethylenehexamine octamethylene tetraphosphonate dimethyl ester ammonium tetraphosphorus acid (APEHAP), was synthesized. The ammonium phosphate active group in APEHAP grafted with cotton fiber via P-O-C covalent bonds, and the phosphonate group prevented metal ions from degrading the flame retardancy of cotton fabrics during washing. The LOI value of the 30 wt.% APEHAP-treated cotton fabric reached 45.2% and remained at 33.6% after 50 laundering cycles (LCs) according to AATCC 61-2013 2A. This indicates that the APEHAP-treated cotton fabric obtained excellent flame retardancy and washing resistance. Scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and X-ray diffraction (XRD) confirmed that the flame retardant APEHAP had little effect on the surface morphology and crystal structure of the cotton fabrics. Thermogravimetry (TG), cone calorimetry, and vertical combustion tests indicated that APEHAP promoted thermal degradation and charring of the cotton fabric during combustion and prevented flame spreading. The APEHAP-treated cotton fabrics maintained their mechanical properties. Graphical abstract: Image, graphical abstract